Compositional strategies with generative scores. Issue 1 (2nd January 2019) - Kim-Boyle, David
ABSTRACT: Generative processes have found broad application in the design of innovative musical forms but it is only comparatively recently through the affordances of modern digital technologies that composers have been able to explore integrating such processes in the real-time creation of musical scores. This paper explores some of these affordances as well as a variety of approaches to some of the key aesthetic and compositional challenges through the analysis of recent works by composers Georg Hajdu, Ryan Ross Smith, Jason Freeman, David Kim-Boyle, and Arne Eigenfeldt.